Light Stimulation of Neurons on Organic Photocapacitors Induces Action Potentials with Millisecond Precision. Issue 9 (18th March 2022) - Schmidt, Tony; Jakešová, Marie; Đerek, Vedran; Kornmueller, Karin; Tiapko, Oleksandra; Bischof, Helmut; Burgstaller, Sandra; Waldherr, Linda; Nowakowska, Marta; Baumgartner, Christian; Üçal, Muammer; Leitinger, Gerd; et al.
Abstract: Nongenetic optical control of neurons is a powerful technique to study and manipulate the function of the nervous system. This research has benchmarked the performance of organic electrolytic photocapacitor (OEPC) optoelectronic stimulators at the level of single mammalian cells: human embryonic kidney (HEK) cells with heterologously expressed voltage‐gated K + channels and hippocampal primary neurons. OEPCs act as extracellular stimulation electrodes driven by deep red light. The electrophysiological recordings show that millisecond light stimulation of OEPC shifts conductance‐voltage plots of voltage‐gated K + channels by ≈ 30 mV. Models are described both for understanding the experimental findings at the level of K + channel kinetics in HEK cells, as well as elucidating interpretation of membrane electrophysiology obtained during stimulation with an electrically floating extracellular photoelectrode. A time‐dependent increase in voltage‐gated channel conductivity in response to OEPC stimulation is demonstrated. These findings are then carried on to cultured primary hippocampal neurons. It is found that millisecond time‐scale optical stimuli trigger repetitive action potentials in these neurons. The findings demonstrate that OEPC devices enable the manipulation of neuronal signaling activities with millisecond precision. OEPCs can therefore be integrated into novel in vitro electrophysiology protocols, and the findings can inspire in vivo applications. Abstract : Using a photocapacitor made from organic pigments, Tony Schmidt and co‐workers successfully stimulate neuronal firing with light. These biocompatible devices convert visible red light into a safe capacitive stimulation for the precise and reliable generation of action potentials in single mammalian cells. This technology enables a wide variety of wireless experimental approaches as well as in vivo applications.